Wax Precipitation in Crude Oil by Coutinho Model Based on Conventional Gas Chromatography Data - Muh Kurniawan; Adiwar Adiwar; Kamarza Mulia; Chairil Anwar (Scientific Contributions Oil and Gas, 2013)
Wax precipitation in crude oils can produce problems in oil production and transportation operations. Prediction is the key of avoidance or remediation of the wax problem of flow assurance. Among the wax prediction thermodynamic model, Coutinho model can be run using limited laboratory data, but the result is comparably accurate. The model requires n-paraffin distribution, which commonly determined by high-temperature gas chromatography (HTGC) analysis. However, only few laboratories could perform the HTGC. Lemigas has abundant database of crude oil with conventional gas chromatography data. An extended n-paraffin distribution was calculated based on the conventional GC data by performing extrapolation and normalization to total wax content. The n-paraffin distribution was applied in Coutinho model to predict wax precipitation of a crude oil sample. The WAT obtained from the model deviated only 2Â°C from DSC data. The result was also valid to DSC data in term of precipitated wax amount along temperature range.